Peran Pembinaan Warga Gereja Bagi Gereja Masa Kini - Harjaya Situmeang; Helma Mesya Cristiani Br Siregar; Megawati Manullang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The nurturing of church members plays a vital role in maintaining the relevance and sustainability of the church amidst various challenges in the modern world. Through proper nurturing, the foundation of faith is strengthened, Christian character is shaped, leadership is developed, and members’ participation in ministry is enhanced. In addressing the realities faced by the contemporary church, effective nurturing becomes a key solution to tackle issues such as individualism, secularism, cultural diversity, and moral crises. With a nurturing approach that is contextual and grounded in the Word of God, church members are equipped to be Christ’s witnesses who live with integrity in society. Therefore, the nurturing of church members not only supports spiritual growth but also ensures the church remains strong, relevant, and impactful in the world.